JIMÉNEZ, Cristina Martín. Os donos do mundo. Campinas: Vide Editorial, 2020. 372 p. - Montans Braga, Luiz Carlos (Revista de Geopolítica, 2023)
Resenha: JIMÉNEZ, Cristina Martín. Os donos do mundo. Campinas: Vide Editorial, 2020 [372 páginas].